SIFAT-SIFAT ALIRAN STRATIFIED DITINJAU DARI KARAKTERISTIK LOKAL (VISUALISASI, LIQUID HOLD-UP DAN SIGNAL PROCESSING) PADA PIPA HORIZONTAL - , Akhmad Zidni Hudaya; , Prof. Dr. Ir. Indarto, DEA, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The visualitation and the time variation of liquid hold-up in a horizontal air-water stratified flow (26.0 mm ID and 9.5 m in total length) has been investigated experimentally. In the present experimental study, the visualisation study was carried-out from the analizing of the visual data obatined from the video camera and the liquid film behavior was investigated by measure the instantaneous local liquid hold-up by using a Constant Electric Current Method (CECM). The principle of this method is on the basis of the conductivity ratio of the two-phase components. Here we used three pairs of liquid hold-up sensors arranged with an axial spacing of 215 mm. As a result it was found that : (1) Both the visual and the signal characterization of the interfacial wave can be used to determine the flow sub-regime in air-water stratified flow. In the smooth stratified sub-regime, no wave were observed and dominant liquid value in probability distribution function (PDF) were cumulated into a narrow. Meanwhile, in the stratified wavy + ripple (SR), stratified wavy + roll (SW), and pseudo-slug (PS) sub-regimes, the interfacial wave were appeared and dominant liquid value in probability distribution function (PDF) were spreaded, (2) the average liquid hold-up increases as the water superficial velocity increases, meanwhile it decreases as the air superficial velocity increases, (3) in the same flow sub-regime, the wave velocity increases as the air superficial velocity increases, and (4) in the stratified wavy+ripple (SR,) dominant frequency decreases as the air superficial velocity increases.